Ecocritical analysis of a selection of short stories from the book Cli-Fi canadian tales of climate change (2025)
Ecocriticism is one of the critical movements that has gained great relevance in recent decades at the international level. This is, partly, due to the fact that in recent times it has been recognized that today's world faces a major problem that corresponds to ecological disasters, which threaten the life of biodiversity and the existence of human beings. In this way, it is considered that science and technology are not enough to combat the global ecological crisis, since such changes and modifications are also found in the way of thinking of individuals, which implies exacerbating their perspective and making them aware through critical literary analysis. Considering the above, it is vital to consider nature in literature and to analyze it critically, as ecologically oriented literature declares a better understanding of nature in its broader meaning. Thus, ecocriticism is an emerging worldwide movement that has distinguished itself from conventional nature by its ethical stance and commitment to the natural world, fostering a connection between the human and non-human world, so, in essence ecocriticism gives emphasis on this ecological consciousness that tends to mitigate man's ego, creating an environmental consciousness in people. From the confrontation of what is perhaps the greatest global crisis of recent times, climate change linked to personal and political indifference has led to several problems that are currently altering the planet and threatening the existence of all beings that inhabit it, science fiction, fantasy, and futuristic works, which transcend traditional end-of-the-world stories by inspiring us to overcome the grim predicted outcomes of our current indifference.